2018
DOI: 10.1039/c7sc03149a
|View full text |Cite
|
Sign up to set email alerts
|

Nickel-catalyzed difunctionalization of allyl moieties using organoboronic acids and halides with divergent regioselectivities

Abstract: We present herein a nickel-catalyzed dicarbofunctionalization of alkenes using readily available organoboronic acids and organic halides in a three-component fashion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
97
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 215 publications
(98 citation statements)
references
References 62 publications
0
97
0
1
Order By: Relevance
“…In this context, very recently, Zhao et al. reported nickel‐catalyzed 1,3 difunctionalization of allylamine moieties …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, very recently, Zhao et al. reported nickel‐catalyzed 1,3 difunctionalization of allylamine moieties …”
Section: Methodsmentioning
confidence: 99%
“…[5] In this context, very recently,Z hao et al reported nickel-catalyzed 1,3 difunctionalization of allylamine moieties. [6] N-Containingc ompounds such as imides [7] and triazole [8] moieties are presenti navarietyo fb iologically and medicinally active compounds, and their synthesis and functionalization have received great attention. Traditionally,t he synthesis of imides have relied primarily on amides with carbonyl chlorides, aldehydes, and acetic anhydride.…”
mentioning
confidence: 99%
“…The pyridine-directed 1,2-diarylation of vinylsilanes with aryl iodides and arylzincs was also achieved through nickel catalysis by the same group. [47] Very recently,apyrimidyl group-directed difunctionalizationo fa liphatic terminal alkenes with arylborons and organohalides was developed by Zhao et al [48] The regioselectivity was highly dependent on the electrophiles. When alkenyl bromides were used, 1,2-alkenylcarbonation took place selectively,w hereas 2,1-alkynylarylation was preferred with alkynyl halides.…”
Section: Nickel Catalysismentioning
confidence: 99%
“…The first one is the employment of 2,2‐disubstituted olefins or geometrically strained olefins, in which the β‐H atom is either absent in the generated C(sp 3 )‐[M] intermediates or hindered to undergo β‐H elimination . Alternatively, for olefins containing an appropriate directing group, a transient C(sp 3 )‐metallacycles might be formed to suppress the β‐H elimination . Apart from the substrate‐dependent strategy, some recently developed first‐row late transition‐metal catalysts demonstrate superior performance in catalyzing dicarbofunctionalization of unactivated olefins with β‐H atom in the generated C(sp 3 )‐[M] intermediates .…”
Section: Introductionmentioning
confidence: 99%
“…Regardless of substantial progress in the past two decades, regioselective dicarbofunctionalization still remains a challenge. In particular, Zhao and co‐workers investigated a Ni‐catalyzed dicarbofunctionalization of allyl moiety of N‐allylpyrimidin‐2‐amine ( 1 ) with organohalides ( 2 ) and organic boronic acids ( 3 ), where challenging regioselectivities were obtained based on the nature of halides. Interestingly, when aryl iodides are utilized for the dicarbofunctionalization of 1 , an intriguing 1,3‐regioselectivity is achieved (Scheme ‐I).…”
Section: Introductionmentioning
confidence: 99%